Appraisal of spring distribution across rain-fed plateau of Pakistan for sustainable development - Arshad Ashraf; Mansoor Ali (Discover Water)
Abstract The water resources of the Himalayan region are under mounting pressure from the demands of a growing population and economic activities. The sustainable management of natural springs is not given enough consideration at the practice and policy levels despite being essential for water security in the Himalayan region of Pakistan. This paper is focused on evaluating spring concentration and associated influential factors in the Islamabad–Rawalpindi region lying in the Rain-fed plateau (called ‘Pothwar’), the sub-Himalayan region of Pakistan. The geospatial techniques were employed to assess the impact of influential environmental factors on the spring resource, while electrical resistivity surveys were carried out to investigate the underlying lithology and aquifer characteristics in the area. Among the total of 311 springs identified in the study area, about 61.4% lie above 1000 m elevation, 31.2% within 500–1000 m, and the rest below 500 m elevation range. The density of springs was found to be maximum, i.e., 0.5 springs/km2, within the 1500–2000 m elevation range, followed by 0.33 springs/km2 within the 2000–2500 m range. The highest spring density, i.e., 0.47 springs/km2, was observed in the 1600–1800 mm rainfall zone, while the least density was noted within the 1000–1200 mm zone (i.e., 0.01 springs/km2). A maximum of about 46.9% of springs were identified in the high (> 0.6) NDVI (Normalized Difference Vegetation Index) class, followed by 45.7% in the moderate (0.4–0.6) NDVI class. The spring density exhibited a close relationship with the mean annual rainfall zones and the NDVI classes, pointing toward the positive influence of wet conditions in sustaining the spring resource in this area. Ecosystem-based land use planning and effective water governance could be effective in improving the spring ecosystem’s health and sustainable spring management. In-depth hydrodynamic and hydrogeologic investigations of the spring resource are essential for understanding its behavior under changing climate and ensuring water security in the region in future.